Tissue-specific SMARCA4 binding at active and repressed regulatory elements during embryogenesis - Attanasio, Catia; Nord, Alex S.; Zhu, Yiwen; Blow, Matthew J.; Biddie, Simon C.; Mendenhall, Eric M.; Dixon, Jesse; Wright, Crystal; Hosseini, Roya; Akiyama, Jennifer A.; Holt, Amy; Plajzer-Frick, Ingrid; et al.

(untitled) (Genome Research, 2014)
The SMARCA4 (also known as BRG1 in humans) chromatin remodeling factor is critical for establishing lineage-specific chromatin states during early mammalian development. However, the role of SMARCA4 in tissue-specific gene regulation during embryogenesis remains poorly defined. To investigate the genome-wide binding landscape of SMARCA4 in differentiating tissues, we engineered a Smarca4FLAG knock-in mouse line. Using ChIP-seq, we identified ∼51,000 SMARCA4-associated regions across six embryonic mouse tissues (forebrain, hindbrain, neural tube, heart, limb, and face) at mid-gestation (E11.5). The majority of these regions was distal from promoters and showed dynamic occupancy, with most distal SMARCA4 sites (73%) confined to a single or limited subset of tissues. To further characterize these regions, we profiled active and repressive histone marks in the same tissues and examined the intersection of informative chromatin states and SMARCA4 binding. This revealed distinct classes of distal SMARCA4-associated elements characterized by activating and repressive chromatin signatures that were associated with tissue-specific up- or down-regulation of gene expression and relevant active/repressed biological pathways. We further demonstrate the predicted active regulatory properties of SMARCA4-associated elements by retrospective analysis of tissue-specific enhancers and direct testing of SMARCA4-bound regions in transgenic mouse assays. Our results indicate a dual active/repressive function of SMARCA4 at distal regulatory sequences in vivo and support its role in tissue-specific gene regulation during embryonic development.